Synthesis, characterization and significant optoelectronic parameters of 1-(7-methoxy-1-benzofuran-2-yl) substituted chalcone derivatives - Coskun, Demet; Gunduz, Bayram; Coskun, Mehmet Fatih (Elsevier Science Bv, 2019)
A new series of benzofuran substituted chalcone derivatives was synthesized by the base-catalyzed Claisen-Schmidt reaction of the 1-(7-methoxy-1-benzofuran-2-yl) ethanone with different aromatic aldehydes to yield 1-(7-methoxy-1-benzofuran-2-yl) substituted chalcone derivatives 3a-e. We investigated in detail the UV spectra, mass extinction, band structure, refractive indices, optical fracture and conductance properties of the benzofuran substituted chalcone derivatives 3a-e. The benzofuran substituted chalcone derivatives 3a-e compounds are suitable for electronic and optoelectronic devices. According to obtained results the electron-withdrawing groups are attached to the ring A, 3c compound gives the worst results for related devices, while the electron-donating groups are attached to the ring A, 3b compound gives the best results for related devices. (C) 2018 Elsevier B.V. All rights reserved.
Keywords: Benzofuran; Chalcone; Refractive indices; Conductance properties; Optoelectronic parameters